Investigating Associations of Omega-3 Fatty Acids, Lung Function Decline, and Airway Obstruction - Patchen, Bonnie K; Balte, Pallavi; Bartz, Traci M; Barr, R Graham; Fornage, Myriam; Graff, Mariaelisa; Jacobs, Jr, David R; Kalhan, Ravi; Lemaitre, Rozenn N; O'Connor, George; Psaty, Bruce; Seo, Jungkyun; et al. (American journal of respiratory and critical care medicine, 2023)
Inflammation contributes to lung function decline and the development of chronic obstructive pulmonary disease. Omega-3 fatty acids have antiinflammatory properties and may benefit lung health. To investigate associations of omega-3 fatty acids with lung function decline and incident airway obstruction in a diverse sample of adults from general-population cohorts. Complementary study designs: ) longitudinal study of plasma phospholipid omega-3 fatty acids and repeated FEV and FVC measures in the NHLBI Pooled Cohorts Study and ) two-sample Mendelian randomization (MR) study of genetically predicted omega-3 fatty acids and lung function parameters. The longitudinal study found that higher omega-3 fatty acid levels were associated with attenuated lung function decline in 15,063 participants, with the largest effect sizes for the most metabolically downstream omega-3 fatty acid, docosahexaenoic acid (DHA). An increase in DHA of 1% of total fatty acids was associated with attenuations of 1.4 ml/yr for FEV (95% confidence interval [CI], 1.1-1.8) and 2.0 ml/yr for FVC (95% CI, 1.6-2.4) and a 7% lower incidence of spirometry-defined airway obstruction (95% CI, 0.89-0.97). DHA associations persisted across sexes and smoking histories and in Black, White, and Hispanic participants, with associations of the largest magnitude in former smokers and Hispanic participants. The MR study showed similar trends toward positive associations of genetically predicted downstream omega-3 fatty acids with FEV and FVC. The longitudinal and MR studies provide evidence supporting beneficial effects of higher levels of downstream omega-3 fatty acids, especially DHA, on lung health.